2020
DOI: 10.1007/s41030-020-00115-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes Among Patients with Cystic Fibrosis Treated with Ivacaftor: 2012–2016 Experience

Abstract: Introduction: In this long-term, postapproval, observational study, data from the US Cystic Fibrosis Foundation Patient Registry and the UK Cystic Fibrosis Registry were used to evaluate the impact of ivacaftor treatment on cystic fibrosis (CF) by comparing outcomes in ivacaftor-treated patients with those in matched untreated comparator patients. Registry data from up to 5 years of ivacaftor availability in the US and up to 4 years of availability in the UK were evaluated. Methods: Starting in the first year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
4
20
0
1
Order By: Relevance
“…Both cross‐sectional and longitudinal studies showed the favorable long‐term outcomes of ivacaftor treatment, both in terms of patients' annual experience during each year of treatment and considering their cumulative experience over time. These data support the conclusion that effective CFTR modulation with ivacaftor leads to disease modification 16–18 …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Both cross‐sectional and longitudinal studies showed the favorable long‐term outcomes of ivacaftor treatment, both in terms of patients' annual experience during each year of treatment and considering their cumulative experience over time. These data support the conclusion that effective CFTR modulation with ivacaftor leads to disease modification 16–18 …”
Section: Discussionsupporting
confidence: 80%
“…Thus, we believe that the observed favorable trends in Italian patients with GMs could probably be explained by widespread ivacaftor treatment. Regarding death and transplantation, no variations were shown in the observed period, but, as in the United Kingdom, 16,18 the low number of events made this evaluation unreliable.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These new therapies resulted in significant benefits for CF patients as described both in Randomized Controlled Trials (RCTs) and studies on data from national CF registries [13,14], but also some adverse events mainly consisting in cough, nasopharyngitis, oropharyngeal pain, and upper respiratory tract infection [15]. In addition, depression, anxiety, sleep paralysis with hypnopompic hallucinations [16] and testicular pain [17] have been reported after initiation of Trikafta therapy.…”
Section: Introductionmentioning
confidence: 99%